Pengaruh Kualitas Website dan Inlfuencer Marketing terhadap Keputusan Pembelian Produk di Marketplace Shopee (Studi Kasus pada Masyarakat Dusun IV Undian Tadukan Raga Deli Serdang) - Ginting, Ayu Taniya; Fikri, Muhammad Hilman; Hutasuhut, Julianto; Hasibuan, Melisa Zuriani (Universitas Batanghari Jambi, 2025)
The purpose of this research is to determine and analyze the influence of website quality and influencer marketing on product purchasing decisions at the Shopee marketplace in the Dusun IV Lottery Tadukan Raga Deli Serdang community. The type of research is quantitative. The population of this study was the entire community of Dusun IV Lottery Tadukan Raga Deli Serdang with 380 respondents. The sample in this study used the Slovin formula, the required sample was 80 samples from the 'Dusun IV Lottery Tadukan Raga' community. The research instrument uses a questionnaire with a Likert scale data measurement scale. Data analysis techniques use validity, reliability and classical assumption tests. The data analysis method uses multiple linear regression with the help of the SPSS program. The results of this research reveal that the quality of the website and influencer marketing simultaneously and partially have a positive and significant effect on product purchasing decisions at the Shopee Marketplace in the Dusun IV Lottery Tadukan Ratga Deli Serdang community.